The role of community education in training program services for the elderly - Imbar Novansyah; Eko Sulistiono; Nuri David Maria Veronika; Irfan Ardi (Curricula: Journal of Curriculum Development, 2024)
The aging process has significant impacts, including physical changes such as decreased vision and hearing, limited movement, and specific health problems in the elderly. Although aging generally brings physical limitations, it encourages high enthusiasm among elderly learners to participate in training programs. So, this research aims to determine the training program services for the elderly. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation studies. Data were analyzed through reduction, presentation, and conclusion drawing with patterns of data analysis findings. This research involved four informants and one program manager. The results of this study reveal that the program manager provides social support, such as (emotional support, tangible support, informational support, and companionship support) and non-social support through learning software and hardware devices. This contributes to the elderly training program services and the effectiveness, attractiveness, and success of the elderly training program.   Abstrak Proses penuaan memiliki dampak signifikan, termasuk perubahan fisik seperti penurunan daya penglihatan, pendengaran, keterbatasan gerakan, dan masalah kesehatan tertentu pada lanjut usia. Meskipun masa penuaan umumnya membawa keterbatasan fisik, hal ini justru mendorong semangat dan antusiasme yang tinggi pada warga belajar lansia dalam mengikuti program pelatihan. Sehingga penelitian ini bertujuan untuk mengetahui pelayanan program pelatihan bagi lanjut usia. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan melalui observasi, wawancara, dan studi dokumentasi. Data dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan dengan pola-pola temuan analisis data. Pada penelitian ini melibatkan empat informan dan satu pengelola program pelatihan. Hasil penelitian ini mengungkapkan bahwa pengelola program memberikan dukungan sosial seperti emosional support, tangible support, informational support, dan companionship support serta dukungan non-sosial melalui perangkat software pembelajaran dan hardware pembelajaran yang secara langsung berkontribusi pada pelayanan program pelatihan lanjut usia dan efektivitas, daya tarik, serta keberhasilan program pelatihan lanjut usia. Kata Kunci: Lanjut usia; layanan pelatihan; pendidikan masyarakat; program pelatihan